The Level of Mesenchymal-Epithelial Transition Autophosphorylation is Correlated with Esophageal Squamous Cell Carcinoma Migration. - Taghehchian, Negin; Moghbeli, Meysam; Mashkani, Baratali; Abbaszadegan, Mohammad Reza (Iranian Biomedical Journal, 2021)
Background: The MET receptor is a critical member of cancer-associated receptor tyrosine kinases and plays an important role in different biological activities, including differentiation, migration, and cell proliferation.Methods: In this study, novel MET inhibitors were introduced and applied on esophageal squamous carcinoma cell line KYSE-30, and the level of proliferation and migration, as well as the activated form of MET receptor protein were assessed in the examined cells. The human KYSE-30 cell line was cultured according to ATCC recommendations. The mRNA level of the MET gene was measured in the examined cell line using the quantitative RT-PCR assay. Cytotoxicity evaluation test was performed at different concentrations of heterocyclic anti-MET compounds (i.e. D1, D2, D5, D6, D7, and D8). Finally, the capability of these compounds in MET receptor inhibition was evaluated using the migration assay and Western blot. All experiments were performed in triplicate and repeated three times with similar results.Results: Cell growth and proliferation were significantly inhibited (p ≤ 0.05) by all the above-mentioned compounds. Moreover, the majority of compounds significantly prevented the cell migration (p ≤ 0.05) and inhibited MET autophosphorylation. Interestingly, the level of phosphorylated MET was significantly correlated with KYSE-30 cell migration.Conclusion: The obtained data introduced and confirmed the biological activities of the mentioned novel compounds in KYSE-30 cells and proposed that the therapeutic inhibition of MET with these compounds may be a powerful approach for inhibiting cancer cell migration and proliferation although some structural optimizations are needed to improve their inhibitory functions.